Association between serum gamma-glutamyltransferase levels and hyperuricemia - Ozgur Tekeli, Seckin; Yagmur Tekeli, Feyza; Eren, Esin; Yilmaz, Necat (Annals of Medical Research, 2021)
Aim: Although the the contribution of gamma-glutamyltransferase (GGT) to hyperuricemia (hUA) has been previously shown in literature, there is not any study showing the contribution of GGT to hUA in a Turkish population. The aim of this study was to investigate both the association between GGT and uric acid (UA) and the contribution of GGT to hUA in the Turkish population.Materials and Methods: This retrospective study was conducted in Antalya, Turkey. A total of 14049 subjects (5521 males and 8528 females) aged > 40 years were recruited and divided into four subgroups according to serum GGT quartiles. Patient demographic data and laboratory results of biochemical parameters were obtained from electronic medical records. Linear regression analysis was applied to GGT quartiles with UA and binary logistic regression analysis was applied to GGT quartiles with hUA.Results: Firstly, serum UA levels were increased across GGT quartiles (p 0.001). Linear regression models showed GGT in the fourth quartile was strong associated with a 0.22 mmol/L (95% confidence interval (CI) 0.16- 0.29, p = 0.001) increase in UA after adjustment. Logistic regression analysis revealed that compared with subjects in the lowest GGT quartile, the adjusted odds ratio (OR) for hyperuricemia in the fourth quartile was 2.62 (95% CI 2.27- 3.01, p = 0.001) after adjustment for age, sex, creatinine, total cholesterol (TC), high density lipoprotein (HDL) cholesterol, triglyceride (TG), glycosylated hemoglobin (HbA1c) and alanine aminotransferase (ALT).Conclusions: Serum GGT is closely associated with serum UA and might contributes greatly to hUA.
Keywords: Cardiovascular disease; Gamma-glutamyl transferase; uric acid